2012
DOI: 10.1038/onc.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed miR-424 expression via upregulation of target gene Chk1 contributes to the progression of cervical cancer

Abstract: MicroRNAs (miRNAs) act as important gene regulators in human genomes and their aberrant expression links to many malignancies. We previously identified a different characteristic miRNA expression profile in cervical cancer from that in cervical normal tissues, including the downregulated miR-424. However, the role and mechanism of miR-424 in cervical cancer still remain unknown. Here, we focused on identifying the tumor-suppressive function and clinical significance of miR-424 and exploring the mechanistic rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 201 publications
(180 citation statements)
references
References 43 publications
8
169
0
3
Order By: Relevance
“…[22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression. We hypothesized that CCNB1 might serve as a Chk1-induced oncogene in colorectal cancer.…”
Section: Discussionsupporting
confidence: 49%
“…[22][23][24][25][26] In contrast to the well-known utility of Chk1 inhibitors in sensitizing tumors to chemotherapy agents, 23,27,28 Chk1 overexpression or downexpression also occurs in some types of tumors, including breast cancer, ovarian cancer, cervical cancer, and neuroblastoma. 22,[29][30][31][32][33] In our study, we found Chk1 mRNA and protein levels were upregulated in colorectal cancer tissues compared with paired normal tissues, and positively correlated with CCNB1 expression. We hypothesized that CCNB1 might serve as a Chk1-induced oncogene in colorectal cancer.…”
Section: Discussionsupporting
confidence: 49%
“…Of the four most effective miRNAs identified, let-7c and miR200b belong to the let-7 and miRNA-200s families, respectively, of which the tumour-suppressor roles in TICs have been well appreciated 8,23,46 , while miR-222 and miR-424 were first identified as TIC-suppressing miRNAs despite a tumoursuppressor role of both miRNAs has been identified in a number of cancers other than HCC [47][48][49][50] . Paradoxically, miR-222 was previously regarded as oncogene in some reports because it could enhance some tumour cell growth by targeting CDK inhibitor p27 in vitro, and was found to be upregulated in HCC and some other types of cancers 42,51,52 ; however, its tumourpromoting role was rarely validated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although the current view in the field is that ATM and ATR signaling inhibits tumor progression rather than promoting cancer (Bartkova et al, 2006;Gorgoulis et al, 2005;Halazonetis et al, 2008), there has been a number of recent reports of overexpression of ATM or ATR, or of activation of the downstream pathways in different cancers (Albiges et al, 2014;Bhatia et al, 2013;Hoglund et al, 2011;Mahajan et al, 2012;Sarmento et al, 2015;Tho et al, 2012;Vadnais et al, 2012;Verlinden et al, 2007;Xu et al, 2013) (see poster). Of note, the addition of an extra allele of Chk1 has even been found to promote Ras-or E1A-mediated transformation more efficiently in comparison to such transformation of wild-type littermates (Lopez-Contreras et al, 2012), suggesting that the ATR-Chk1 axis has a pro-malignant transformation role.…”
Section: Box 1 Relevance Of Atm and Atr Signaling In Cancermentioning
confidence: 99%